The effect of bimodality on tensile properties of filled silicone networks (eXPRESS Polymer Letters, 2008)
The effect of blending short and long chains (bimodality) silicone prepolymer, in the presence of a filler (17.2 and 30.2% w/w) on tensile properties such as ultimate tensile strength (UTS), percent elongation at break (% Eb), 100% modulus and elastic modulus has been investigated. The content of short chain prepolymer was varied from 0–69% and 0–58% for 17.2 and 30.2% filled silicones respectively. It was found out that the tensile properties were enhanced for the low filled (17.2%) silicone networks while in the case of highly filled (30.2%) silicone networks; the bimodality adversely affected the tensile properties such as UTS, % Eb. It is also observed that the optimum in these properties was recorded at 95 mol% as compared to 70 mol% of short chain prepolymer for unfilled silicone system. The phenomenon of improvement in mechanical properties due to bimodality in this system has been discussed.